Evaluation of ground information with respect to EPB tunnelling for the Thessaloniki metro, Greece - Marinos, P. G.; Novack, M.; Benissi, M.; Stoumpos, G.; Panteliadou, M.; Papouli, D.; Marinos, V.; Korkaris, K. (Bulletin of the Geological Society of Greece, 2007)
The Thessaloniki Metropolitan Railway comprises two separate 6 m diameter parallel tunnels with an 8 km stretch each and 13 stations. The geology of the urban area of Thessaloniki is characterised by the presence of Neogene and Quaternary deposits. The base formation for the project area is a very stiff to hard red clay, dating to Upper Miocene-Pliocene. Upon this formation, Quaternary sediments have been deposited, most of which comprise sand and/or gravel in a clay-silt dominated matrix, covered in places by anthropogenic fill. Ground investigation campaigns incorporated a significant number of sampling boreholes and in situ and laboratory testing. This information was elaborated in order to obtain a better geological understanding and a geotechnical zonation of the ground with respect to mechanized tunnelling. EPB M appears to be the reasonable choice for the project in all aspects of tunnel safety and tunnelling performance. The characteristics and parameters of the soils and the hydrogeological regime directed towards this selection and it is expected that all the objectives, such as settlement and ground movements control, water table level maintenance and adequate performance, will be met by an EPBM provided it is properly operated